2017
DOI: 10.15406/ijcam.2017.09.00314
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Cellular Energy (ACE) Pathway as the Foundation for a New Paradigm in Medicine

Abstract: Physicians currently regard most chronic illnesses as biochemical disorders that require long-term pharmaceutical therapy. While restoring biochemical balance in the diseased cells, pharmaceuticals can affect similar biochemical pathways in normal cells. As expected, this commonly leads to adverse clinical side effects. Given an adequate amount of energy, cells can potentially work at restoring their own normal functions. A major boost to energy-based medicine is the identification of an energy pathway in livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Life requires energy, as does Nature's adaptations to altered circumstances. Three levels of energy can be envisioned [8]. The lowest level is for survival.…”
Section: Nature's Allostasis and Its Tipping Pointsmentioning
confidence: 99%
“…Life requires energy, as does Nature's adaptations to altered circumstances. Three levels of energy can be envisioned [8]. The lowest level is for survival.…”
Section: Nature's Allostasis and Its Tipping Pointsmentioning
confidence: 99%
“…Currently, there are no published drinking water studies involving structured water and its effects on age-related diseases. However, a few water drinking studies have shown that structured water is associated with human longevity, and rehydration at the cell level can be enhanced [97][98][99][100][101][102][103][104][105][106][107][108][109][110][111]. Two drinking studies with human subjects showed that intracellular water content improved after drinking different forms of structured water.…”
Section: Effects Of Drinking Sw Water On Health and Longevitymentioning
confidence: 99%